“Work? I have learned to live with it.” A Biographical perspective on Work, Learning and Living... ...More than Just a Story - Veerle Stroobants; Danny Wildermeersch (Adult Education Research Conference, 2000)
A biographical perspective on living and learning is more than an outgrowth or continuation of current individualisation processes. Stories of women about work and life, show that the notion of biography holds possibilities to create other meaningful connections between individual and society than those nowadays judged problematic or at loss.